Integrating Al-Syāfi‘I Thought and Geospatial Instruments: Google Earth as Qibla Calibration Tools in Aceh - Machzumy Machzumy; Kusdiyana Kusdiyana; Muhammad Khalil Mubarraq (Islamic Astronomy Department, Sharia and Law Faculty, 2026)
In Aceh Province, where the Syāfi‘I school of jurisprudence predominates, the principle of jihāt al-Kaaba has traditionally guided Muslim communities in determining the qibla. This study explores the intersection between classical jurisprudential perspectives and contemporary geospatial approaches, focusing on the extent to which mosques across Aceh are aligned with the Kaaba. Empirical data were collected through the measurement of mosque orientations and their comparison with the astronomically determined direction of the qibla. The findings reveal a measurable divergence between traditional mosque alignments and precise geospatial calculations. On average, the surveyed mosques are oriented at 289.91350 (2890 54’ 48”), while the exact direction of the jihāt al-Kaaba is 292.55050 (2920 33’ 1”). This discrepancy results in a mean deviation of 2.6370 (20 38’ 13”), with considerable variation at the individual mosque level. The Great Mosque Sulthan Jeumpa in Bireun demonstrates the highest accuracy, deviating only 0.320 (00 19’ 12”), while the Great Mosque Lhoksukon in North Aceh shows the largest misalignment at 16.980 (160 58’ 48”). These variations highlight the uneven application of qibla determination methods, ranging from traditional observational practices to modern geospatial technologies. The integration of tools such as Google Earth provides communities with not only practical accuracy but also spiritual reassurance, reinforcing confidence in qibla orientation. Ultimately, this study underscores the importance of combining fiqh based principles with contemporary scientific methods to ensure both symbolic fidelity and empirical precision in religious practice.